2022
DOI: 10.1590/1806-9282.20211253
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios of overweight children and adolescents

Abstract: OBJECTIVE: This study aimed to compare neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio of overweight children and adolescents with the eutrophic ratios and to verify whether these ratios are associated with age, inflammation, Z-score of body mass index, and waist-to-height ratio. METHODS: This is a cross-sectional study involving 64 overweight and 106 eutrophic children and adolescents. Data on weight, height, and waist circumference (body mass index and waist-to-height ratio), blood count (neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…When we examine studies conducted on obese children, Anik et al reported that PLR is not different in obese adolescents compared to healthy controls [30]. Likewise, no difference was found in the study conducted by Yazaki et al [31].…”
Section: Discussionmentioning
confidence: 74%
“…When we examine studies conducted on obese children, Anik et al reported that PLR is not different in obese adolescents compared to healthy controls [30]. Likewise, no difference was found in the study conducted by Yazaki et al [31].…”
Section: Discussionmentioning
confidence: 74%
“…Mărginean et al [11] also found comparable NLR values between children and adolescents with obesity and normal-weight individuals. In a study performed on adolescents with obesity, Dilek et al [43] reported that PLR values were comparable between adolescents with obesity and healthy controls, while Yazaki et al [44] detected no correlation between NLR and BMI in their study of children with obesity. In contrast, Aydin et al [45] observed a significant increase in NLR and PLR values in adolescents with obesity compared to healthy controls.…”
Section: Discussionmentioning
confidence: 93%